Twisted fairy tale: Narrative functions and dramatic personae in William Faulkner`s A Rose for Emily - Sa'adah, Sufi Ikrima; Hutami, Nestiani; Mufidah, Zakiyatul (EduLite: Journal of English Education, Literature and Culture, 2024)
William Faulkner`s A Rose for Emily is narrated in a complex narrative structure, thus, making it difficult to follow the story`s chronology despite its relatively short form. This article provides a different approach using Propp`s narratology to show that the story can be read as a modern fairy tale but with some twisted elements. The analysis focuses on the sequence of events based on Propp`s 31 narrative functions. The analysis also highlights the characters performing the functions following Propp`s seven types of dramatis personae. The findings reveal that the events in A Rose for Emily conform to some of the narrative functions of a fairy tale. The initial situation introduces Emily as the heroine of the story, followed by her father's death, which represents the absentation function. In the middle of the narrative, the villainy function serves as the complication of the story. The story`s end is also similar to a fairy tale by the wedding function. However, these fairy tale elements are presented in twisted ways. Emily was introduced only when she died, and she poisoned Homer to be able to live with him ever after. Meanwhile, Emily and Homer also provide twists as the story's heroine and villain.